PENERAPAN MODEL PENUGASAN (ASSIGNMENT MODEL) HUNGARIAN UNTUK OPTIMALISASI ALOKASI JADWAL KHOTBAH PENATUA GUNA MEMINIMALKAN INDEKS KESENJANGAN KONTEKSTUAL: (Studi Operasional Manajemen Pelayanan Liturgi Berbasis Komputasi QM for Windows) - Refani Abednego Samosir; Jhon Kristopel Manalu; Parapat Gultom (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Optimization of the assignment of ministers of the Word (Preachers) across various categorical worship services constitutes one of the strategic responsibilities of the Congregational Leadership to ensure the relevance of theological messages and the fulfillment of the congregation's spiritual needs. This study aims to determine the optimal assignment combination of four Elders/Preachers (Preacher 1, Preacher 2, Preacher 3, and Preacher 4) to four specific categorical worship positions (General/Adult Worship, Youth/Young Adult Worship, Sunday School/Children's Worship, and Men's/Elderly Worship) at GMI. A quantitative approach was applied through the Assignment Model with the minimization criterion of the "Contextual Gap Index" (CGI) executed using QM for Windows software version 5. Input data were obtained objectively through the conversion of linearity scores of service gifts, age profiles, and historical records of congregational evaluation satisfaction. The results of the program execution using the Hungarian algorithm demonstrated that the quantitative-based assignment successfully reduced the total gap index from 34 points to only 22 points per monthly cycle. This reduction in inefficiency index of 35.29% proves the effectiveness of the congregational leadership's role in applying management science for more optimal stewardship of worship services.